TANGGUNG JAWAB NEGARA ATAS PELINDUNGAN OBJEK SIPIL PADA KONFLIK BERSENJATA BERDASARKAN PRINSIP PROPORSIONALITAS DALAM HUKUM HUMANITER INTERNASIONAL: STATE RESPONSIBILITY FOR THE PROTECTION OF CIVILIAN OBJECTS IN ARMED CONFLICT BASED ON THE PROPORTIONALITY PRINCIPLE IN INTERNATIONAL HUMANITARIAN LAW - Fitriliani, Yulia; Sujatmoko, Andrey (Fakultas Hukum Universitas Trisakti, 2023)
In IHL, there is the principle of proportionality, namely in the case of carrying out an attack, both the means and the method, the damage that will be suffered by the civilian population or civilian objects must be proportional in nature and not excessive in relation to the acquisition of real and direct military benefits that can be predicted as a result of the attack on military targets. But in reality, in an armed conflict, there must be many victims, both from those who participate and those who do not participate in the war, and cause damage to civilian objects, either intentionally or unintentionally. Therefore, the research problem is how the act of attacking civilian objects in armed conflict based on the principle of proportionality; and how the state's responsibility for the protection of civilian objects in armed conflict based on the principle of proportionality. The results of the research concluded that (1) During armed conflict, it is still necessary to fulfill the principles and provisions in IHL, one of which is the principle of proportionality based on Article 57 paragraph (2) (a) (i to iii) of Additional Protocol I, 1977. The party that will carry out the attack has the obligation to gather information in advance before and at the time of the attack in order to know that the target to be attacked is a military target, not a civilian object. Then take all precautions in choosing the means and methods of attack, so that the damage to be suffered by the civilian population or civilian objects is proportionate and not excessive in relation to the acquisition of real and direct military advantage; (2) In the event of an attack on civilian objects in armed conflict, the attacking state must be responsible for all internationally wrongful acts, which result in damage and loss. This is stipulated in ARSIWA 2001, Article 2. In IAC, the 1907 Hague Convention IV, Article 3; the 1949 Geneva Conventions, namely Article 51 of Geneva Convention I, Article 52 of Geneva Convention II, Article 131 of Geneva Convention III, and Article 148 of Geneva Convention IV, 1949; Additional Protocol I, 1977, Article 91 apply. In NIAC, Article 3 of the Geneva Conventions 1949 applies.